Phage-derived protein induces increased platelet activation and is associated with mortality in patients with invasive pneumococcal disease - Tunjungputri, R.N.; Mobegi, Fredrick; Cremers, A.J.; van der Gaast-de Jongh, C.E.; Ferwerda, G.; Meis, J.F.; Roeleveld, N.; Bentley, S.D.; Pastura, A.S.; van Hijum, S.A.F.T.; van der Ven, A.J.; de Mast, Q.; et al. (AMER SOC MICROBIOLOGY, 2017)
To improve our understanding about the severity of invasive pneumococcal disease (IPD), we investigated the association between the genotype of Streptococcus pneumoniae and disease outcomes for 349 bacteremic patients. A pneumococcal genome-wide association study (GWAS) demonstrated a strong correlation between 30-day mortality and the presence of the phage-derived gene pblB, encoding a platelet-binding protein whose effects on platelet activation were previously unknown. Platelets are increasingly recognized as key players of the innate immune system, and in sepsis, excessive platelet activation contributes to microvascular obstruction, tissue hypoperfusion, and finally multiorgan failure, leading to mortality. Our in vitro studies revealed that pblB expression was induced by fluoroquinolones but not by the beta-lactam antibiotic penicillin G. Subsequently, we determined pblB induction and platelet activation by incubating whole blood with the wild type or a pblB knockout mutant in the presence or absence of antibiotics commonly administered to our patient cohort. pblB-dependent enhancement of platelet activation, as measured by increased expression of the ɑ-granule protein P-selectin, the binding of fibrinogen to the activated ɑ IIbβ3 receptor, and the formation of platelet-monocyte complex occurred irrespective of antibiotic exposure. In conclusion, the presence of pblB on the pneumococcal chromosome potentially leads to increased mortality in patients with an invasive S. pneumoniae infection, which may be explained by enhanced platelet activation. This study highlights the clinical utility of a bacterial GWAS, followed by functional characterization, to identify bacterial factors involved in disease severity.